The extent to which safety and health is provided in ECD learning environment in urban schools in Bulawayo Metropolitan Province - Mutazu, Grace (Midlands State University, 2019)
The purpose of the study was to find out the extent to which safety and health is provided in ECD Learning environment in urban schools in Reigate District in Bulawayo Metropolitan Province. Data were generated using qualitative research. The researcher used the descriptive survey design to explore issues related to health and safety in ECD centres. It allowed the use of interview and observations guides. The sample of participants comprised of two school heads, six ECD teachers, two TIC’s and twenty ECD pupils purposively selected from two schools in Reigate District. The research instruments used exposed that safety and health is provided in ECD learning environments in Airport Cluster in Reigate District to a lesser extent due the negative attitudes of teachers during implementation of health and safety issues, under qualification of some of the teachers, lack of financial resources to support this worth cause and too large teacher pupil ratio. The researcher then recommended that the government, therefore should facilitate the objective and effective implementation of health and safety policies in ECD learning areas by the use of intermediaries such as school administrator’s teachers, family members, SDCs, NGOs and other stakeholders. There was need for refurbishment of school buildings and grounds and the need for them to be maintained to be free of health and safety hazards.